Cellini's Perseus and Medusa and the Loggia dei Lanzi : configurations of the body of state - Corretti, Christine (Art and material culture in Medieval and Renaissance Europe, 2015)
Cellini's Perseus and Medusa and the Loggia dei Lanzi: Configurations of the Body of State explores the role that maternal influence played in the formation of Cosimo I de' Medici's absolutist state.